2021
DOI: 10.1177/15353702211034144
|View full text |Cite
|
Sign up to set email alerts
|

Predictive values of sST2 and IL-33 for heart failure in patients with acute myocardial infarction

Abstract: Timely prediction of the risk of heart failure in acute myocardial infarction patients is critical for better prognosis. This article aims to evaluate the predictive value of serum soluble growth stimulation expressed gene 2 (sST2) and interleukin-33 in patients with acute myocardial infarction complicated by heart failure. A total of 42 healthy controls and 144 acute myocardial infarction patients were recruited in the study. According to Killip cardiac function classification as the basis for concurrent hear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 36 publications
0
8
0
Order By: Relevance
“…This scenario is supported by significantly increased sST2 and IL-33 levels in patients with acute myocardial infarction as compared to normal healthy controls, with a further increase in patients with heart failure. 60 Moreover, protein contents of IL-33 and ST2 increased in a mouse myocardial infarction model, whereas a reduced-deubiquitinase USP17-mediated IL-33 degradation improved cardiomyocyte apoptosis. 61 In a rat myocardial infarction model, treatment with bisoprolol, a beta-blocker, for 4 weeks improved cardiac function and reduced serum sST2 levels, and decreased infarct size when compared with the placebo group.…”
Section: Il-33 In Myocardial Infarctionmentioning
confidence: 98%
See 1 more Smart Citation
“…This scenario is supported by significantly increased sST2 and IL-33 levels in patients with acute myocardial infarction as compared to normal healthy controls, with a further increase in patients with heart failure. 60 Moreover, protein contents of IL-33 and ST2 increased in a mouse myocardial infarction model, whereas a reduced-deubiquitinase USP17-mediated IL-33 degradation improved cardiomyocyte apoptosis. 61 In a rat myocardial infarction model, treatment with bisoprolol, a beta-blocker, for 4 weeks improved cardiac function and reduced serum sST2 levels, and decreased infarct size when compared with the placebo group.…”
Section: Il-33 In Myocardial Infarctionmentioning
confidence: 98%
“…This scenario is supported by significantly increased sST2 and IL-33 levels in patients with acute myocardial infarction as compared to normal healthy controls, with a further increase in patients with heart failure. 60…”
Section: Role Of Il-33 In Cardiac Diseasementioning
confidence: 99%
“…Acute myocardial infarction (AMI) is a kind of heart disease in cardiology due to the blockage of the coronary arteries. 1 AMI can cause a sudden decline in blood flow, myocardial hypoxia, necrosis, ischaemia and result in complications including chest pain and arrhythmia. 2 The onset of AMI is fast and the disease progresses quickly, and if the treatments are not timely provided, AMI can be life-threatening.…”
Section: Introductionmentioning
confidence: 99%
“…Acute myocardial infarction (AMI) is a kind of heart disease in cardiology due to the blockage of the coronary arteries 1. AMI can cause a sudden decline in blood flow, myocardial hypoxia, necrosis, ischaemia and result in complications including chest pain and arrhythmia 2.…”
Section: Introductionmentioning
confidence: 99%
“…It is thus particularly important to predict the risk of heart failure in patients with AMI. Recent studies have shown that carbohydrate antigen 125, brain derived neurotrophic factor, serum soluble growth stimulation expressed gene 2, and interleukin-33 are effective predictors of heart failure in patients with AMI [ 12 , 13 ]. However, these indicators are rarely measured in clinical trials, which largely limits their clinical practice.…”
Section: Introductionmentioning
confidence: 99%